Non-destructive Evaluation of Oil Content and Carotene in Oil Palm Fresh Fruit Bunches Based on Optical Properties Using Partial Least Square (PLS) - Suaidah Rahmi; Dinah Cherie; Ifmalinda Ifmalinda; Muhammad Makky (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Crude palm oil (CPO) is a raw material for making cooking oil that comes from palm oil, which is greatly influenced by the quality of oil palm fresh fruit bunches (FFB). Oil and carotene content in the FFB influence the quality of palm oil. The oil content is usually determined using a chemical method (Soxhlet extraction) which is time consuming and destructive. This research aimed to predict the oil and carotene content contained in oil palm FFB using partial least square (PLS). In this research, the sample used was the Tenera variety with a maturity of 140-160 day after anthesis (DAA) and 200-220 DAA. The nondestructive method involves recording images using an optical camera, which produces RGB and L*a*b* values. Results showed that PLS predicts the relationship between optical properties and oil and carotene content in palm oil. Non-destructive prediction results using PLS provided consistently correlation of L*a*b* values with estimated oil and carotene content in the FFB. Keywords: Non-destructive, Optical properties, Fresh fruit bunch, Oil palm.